Speech Therapy Work with Elementary-School Children with Autism Spectrum Disorders and Intellectual Disabilities - S.V. Andreeva (Moscow State University of Psychology and Education, 2020)
Asynchronous neuropsychic development of children with autism spectrum disorders (ASD) involves not only a personalized approach, which takes into account behavioral characteristics of children during their education and correction, but also the development of new habilitation programs. The structural components of speech therapy work with children with ASD and intellectual disabilities presented. The most important motivational and incentive stage of work with children with behavioral features, which includes the formation of special educational environment, described in detail. As part of a comprehensive speech therapy work, basic differentiated tasks are determined depending on the degree of formation, impaired speech and potential developmental opportunities, from the establishment of sufficient articulatory capabilities to the development of verbal or alternative communication. The main directions of speech therapy work on the formation of speech function in primary schoolchildren studying in programs for children with intellectual disabilities presented. Experience of speech therapy practice in correctional work with children with writing and reading disorders presented.